ALGUNS EFEITOS DO FLUOMETRON SOBRE O CRESCIMENTO INICIAL DA RAIZ DO FEIJOEIRO (ð˜—ð˜©ð˜¢ð˜´ð˜¦ð˜°ð˜ð˜¶ð˜´ ð˜·ð˜¶ð˜ð˜¨ð˜¢ð˜³ð˜ªð˜´ L.) - Marinis, Giorgio de; Ferreira, AristÃ©ia A. A.; Santos, Rozely F. dos; Delitti, Welington B. C. (REVISTA DE AGRICULTURA, 2020)
ALGUNS EFEITOS DO FLUOMETRON SOBRE O CRESCIMENTO INICIAL DA RAIZ DO FEIJOEIRO (ð˜—ð˜©ð˜¢ð˜´ð˜¦ð˜°ð˜ð˜¶ð˜´ ð˜·ð˜¶ð˜ð˜¨ð˜¢ð˜³ð˜ªð˜´ L.)